Low Risk for Local and Systemic Complications After Primary Repair of 1626 Achilles Tendon Ruptures. Issue 3 (June 2017) - Rensing, Nicholas; Waterman, Brian R.; Frank, Rachel M.; Heida, Kenneth A.; Orr, Justin D.
Introduction. Historically, Achilles tendon repairs and other surgeries about the hindfoot have demonstrated a significantly higher rate of wound healing complications and surgical site morbidity. The purpose of this study was to evaluate the comprehensive complication profile and risk factors for adverse short-term, clinical outcomes after primary repair of Achilles tendon ruptures. Methods. Between the years 2005 and 2014, all cases of primary Achilles tendon repair (Current Procedural Terminology code 27650) entered into the National Surgical Quality Improvement Project (NSQIP) database were extracted for analysis. Primary outcomes of interest were rates of total complication, reoperation, and rerupture within 30 days of index surgery. Independent risk factors associated with these selected endpoints were assessed with chi-square and logistic regression analysis and odds ratios with 95% confidence intervals were used to express relative risk. Results. Of 1626 patients with an average age of 44 years (SD 13.3), the average ASA classification was 1.69 and hypertension (20.7%), morbid obesity (8.3%), and diabetes (4.9%) were among the most common medical comorbidities. A total of 28 (1.7%) patients sustained perioperative complications, including 1.3% with local complications (0.7% superficial wound infection, 0.4% wound disruption) and no cases of peripheral nerve injury or early repair failure. Systemic complications occurred in 0.4%, most commonly with deep venous thrombosis or nonfatal thromboembolism. Preoperative albumin was independently associated with an increased risk of local wound complications (odds ratio [OR] 28.67; 95% CI 1.42-579.40; P = .029). Chronic obstructive pulmonary disease (OR 22.33, 95% CI 2.49-199.81; P = .006) and bleeding disorder (OR 14.83, 95% CI 1.70-129.50; P = .015) were more likely to result in a systemic complication, and preoperative creatinine correlated with an increased risk of any complication (OR 6.11, 95% CI 1.15-32.34; P = .033). In total there were 5 (0.3%) readmissions with 2 (0.1%) unplanned reoperations attributed to local wound complications. Conclusion. Among a broad-based demographic of the United States, the rate of local wound complications was exceedingly low in the short-term perioperative period, although this risk may be significantly magnified with subtle decreases in albumin levels. Preoperative risk stratifications should carefully scrutinize for subtle abnormalities in nutritional parameters and renal function prior to undergoing Achilles surgery. Levels of Evidence: Therapeutic, Level II: Prospective, comparative trial